Sistema PACS-CNR, una propuesta tecnológica - Gutiérrez Martínez, Josefina; Martínez Martínez, Alfonso; Núñez Gaona, Marco Antonio; Reyes Marín, Baltasar; Delgado Esquerra, Ruth Evelyn; Muñoz de Cote Flores, José Enrique; Chávez Avelar, Norberto (Revista Mexicana de Ingenieria Biomedica, 2003)
The Centro Nacional de Rehabilitación, in Mexico City, decided to rely on digital imaging technology, specifically PACS, to capture, transmit, record, display, store and archive all diagnostic images captured by the division of radiology. The CNR’s physical facility and films amount raised some serious logistical problems for the management of diagnostic images. This paper presents the analysis carried out about the advantages of installing a PACS in this Center. The PACS will be installed primarily to improve patient throughput, care, and productivity by making diagnostic images and related clinical information more readily available to clinicians and radiologists, to reduce storage needs, and to reduce the incidence of lost or misplaced film. The division of radiology will improve its image and information access with a network distribution and digital archiving management, together with the improved radiologist and technician efficiencies. In addition, we propose to design, develop and implement the PACSCNR system, to reduce the dependence of the state-of-the art digital technology and operating-maintenance costs.